Automated Greulich-Pyle bone age determination in children with chronic kidney disease - Nüsken, Eva; Tönshoff, Burkhard (Pediatric nephrology, 2015)
BackgroundGrowth restriction and retarded bone age are common findings in children with chronic kidney disease (CKD). We compared the automated BoneXpert™ method with the manual assessment of an X-ray of the non-dominant hand.MethodsIn this retrospective multicenter study, 359 patients with CKD stages 2-5, aged 2-14.5 (girls) or 2.5-17 years (boys) were included. Bone age was determined manually by three experts (according to Greulich and Pyle). Automated determination of bone age was performed using the image analysis software BoneXpert™.ResultsThere was a strong correlation between the automatic and the manual method (r = 0.983, p < 0.001). The automatic method tended to generate higher bone age values (0.64 ± 0.73 years) in the younger patients (4-5 years) and to underestimate retardation or acceleration of bone age. The so-called “bone health index” (BHI) was reduced in comparison to the reference population. Bone health index standard deviation score (BHI-SDS) was not related to the stage of CKD, but weakly negatively correlated with plasma PTH concentrations (r = 0.12, p = 0.019).ConclusionsBoneXpert™ allows an objective, time-saving, and in general valid bone age assessment in children with CKD. Possible underestimation of retarded or accelerated bone age should be taken into account. Validation of the BHI needs further study.
Gesehen am 11.04.2017